Mój ból jest większy niż twój: Proces upamiętniania KL Plaszow (Politeja, 2023)
MY PAIN IS GREATER THAN YOURS: THE PROCESS OF COMMEMORATING KL PLASZOWThis article presents an accompanying description of the process involved in commemorating the former labor and concentration camp, Plaszow. The actors involved primarily differ in the function they desire to attribute to the memorial, while the strong emotions accompanying them are primarily a consequence of the process’s underlying cause – death ingrained in the post-camp landscape. Engagement in the process evokes suffering, which limits the possibilities for dialogue surrounding commemoration. Recently, the appointment of a caretaker for the site of memory, the KL Plaszow Museum, has proven to be the most influential factor in the dynamics of the process. Given that the museum is an enduring institution, there is now a strong need to explore new forms of mediation that facilitate understanding. In the author’s view, specialists in culture studies, with their expert competencies, can serve as neutral intermediaries bridging the diverse expectations of the actors.